Reassessing the Ethicality of Some Common Financial Practices - Bagus, Philipp (Journal of business ethics, 2016)
Depositors have perceived banks as acting unethically during the most recent recession. One area of consternation is the ambiguity of the legal obligations entailed by the deposit contract when it is backed with only fractional reserves. In this article, we apply an existing analysis of the legitimacy and ethicality of banking practices to a wider range of financial transactions, including insurance policies, securities lending, perpetual bonds, and callable loans. Securities lending in particular creates rights violations analogous to those in fractional-reserve banking. Both callable loans and perpetual bonds have clear legal obligations which are not inherently problematic, though we herein clarify what these obligations are. Finally, we apply our ethical framework to demonstrate that insurance products are distinct from banking deposit contracts, and that perceived parallels between the two products underestimate these differences.